Case report: Systemic air embolism after percutaneous microwave ablation of an unresectable metastatic lung lesion - Tang, Wei; Zhu, Fandong; Yang, Jianfeng; Wang, Ting; Zhao, Zhenhua; Feng, Jiangfeng (Frontiers in Oncology, 2024)
Systemic air embolism, though rare, poses a significant risk as a complication of CT-guided lung lesion ablation. This condition often arises from the formation of a transient bronchovascular fistula, which can occur when a needle punctures the lung or accidentally breaches a pulmonary vein. In this report, we present a case involving acute cerebral infarction resulting from retrograde venous embolism linked to a fistula between the pleural cavity and pulmonary artery after pulmonary ablation. The patient demonstrated clear signs and symptoms but ultimately recovered fully and was discharged without lasting effects. This case underscores the critical need for ongoing vigilance and proactive measures to prevent air embolism during such medical procedures.